Multiomic approach for bioprospection: Search of new toxins of Brazilian sea anemone Bunodosoma caissarum - Mazzi, Maria Eduarda Esquinca [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Sea anemones are sessile invertebrates belonging to the Cnidaria phylum and their sur- 14 vival and evolutive success is highly related to the ability of producing and fast inoculating venom, 15 with the presence of potent toxins. In this study, a multiomic approach was performed to character- 16 ize the protein composition of the tentacles and mucus of Bunodosoma caissarum, a species of sea 17 anemone from the Brazilian coast. The tentacles transcriptome resulted in 23444 annotated genes, 18 of which 1% showed similarity with toxins or proteins related to toxin activity. In the proteome 19 analysis, 430 polypeptides were consistently identified, being 316 of them more present in the ten- 20 tacles while 114 were enriched in the mucus. Tentacle proteins were mostly enzymes followed by 21 DNA and RNA associated proteins, while in the mucus most proteins were toxins. In addition, pep- 22 tidomic allowed the identification of large and small fragments of mature toxins, neuropeptides and 23 intracellular peptides. In conclusion, herein integrated omics identified genes previously unknown 24 or uncharacterized besides 23 toxin-like proteins of therapeutic potential, improving the under- 25 standing about tentacle and mucus composition of sea anemones.

Anêmonas são invertebrados sésseis pertencentes ao Filo Cnidaria e sua sobrevivência e sucesso ecológico estão altamente relacionados à sua habilidade de produzir e rapidamente inocular veneno, com a presença de toxinas potentes. Neste estudo, uma abordagem multiômica foi realizada para caracterizar a composição proteica dos tentáculos e muco da Bunodosoma caissarum, uma espécie de anêmona da costa brasileira. O transcriptoma do tentáculo resultou em 23444 genes anotados, dos quais 1% mostrou similaridade com toxinas ou proteínas relacionadas à atividade tóxica. Na análise proteômica, 430 polipeptídeos foram consistentemente identificados, sendo 316 destes mais presentes nos tentáculos enquanto 114 estavam enriquecidas no muco. Proteínas do tentáculo eram majoritariamente enzimas, seguidas por proteínas associadas a DNA e RNA, enquanto no muco, a maior parte eram toxinas. Além disso, a peptidômica permitiu a identificação de fragmentos pequenos e grandes de toxinas maduras, neuropeptídeos e peptídeos intracelulares. Em conclusão, as ômicas integradas identificaram genes previamente desconhecidos e não caracterizados, além de 23 proteínas tipo toxinas de potencial terapêutico, aumentando a compreensão sobre a composição de tentáculos e muco de anêmonas marinhas.
Abordagem multiômica para bioprospecção: Busca de novas toxinas da anêmona brasileira Bunodosoma caissarum
Keywords: Cnidaria; Anêmona; Toxinas; Neuropeptídeos; Sea anemone; Omics; Toxins; Intracellular peptides; Neuropeptides